If it's not what You are looking for type in the equation solver your own equation and let us solve it.
c+33/4=12/3
We move all terms to the left:
c+33/4-(12/3)=0
We add all the numbers together, and all the variables
c+33/4-4=0
We add all the numbers together, and all the variables
c-4+33/4=0
We multiply all the terms by the denominator
c*4+33-4*4=0
We add all the numbers together, and all the variables
c*4+17=0
Wy multiply elements
4c+17=0
We move all terms containing c to the left, all other terms to the right
4c=-17
c=-17/4
c=-4+1/4
| 20=24–4s | | 13=21-4w | | 28=9+8+c | | 10=21/4*t | | 2(-4+2x)-2(1+6x)=6 | | m/3+5=9 | | 6w+51/2=7 | | -6n+11=-67 | | m3+5=9 | | n-15=6 | | 2x+11=6/4x+33/4 | | 6w+1.5=7 | | 8x+36=5+60 | | 6=2((-4)+2x)-2(1+6x | | 2=20–2y | | 4w+15=w-3 | | 6v-11v-14=4 | | -15+8q=25 | | 5b-b=3b | | 2(a–8)+7=5(a+2)–3a–19 | | h/3+45=52 | | -7/9x=-1/2 | | y=5X+.50 | | 3/412c-4=15c+15 | | 5x+23=23 | | 88m=11 | | z/8–2=1 | | z/8– 2= 1 | | 7x=15=12x=5 | | 5/6n=$150.60 | | -14/3=-7u | | 4(-3/2v+1)-6=5v-(11v+1) |